2010
DOI: 10.2341/09-051-l
|View full text |Cite
|
Sign up to set email alerts
|

Shear Bond Strength of Three Different Nano-Restorative Materials to Dentin

Abstract: Nano glass ionomer exhibited significantly lower shear bond strength compared to nano-composites. The self-etch adhesive showed higher shear bond strength than etch&rinse adhesive for both nanofill and flowable nanofill composites. Materials and Methods: Sixty human molars were ground flat, exposing the dentin surfaces, and they were randomly divided into five groups according to the restorative materials and adhesive systems used (n=12/group). The restoratives were applied to all dentin surfaces according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 33 publications
2
23
1
8
Order By: Relevance
“…In the SEM photomicrograph of the fractured surface of the nano-filled RMGI bonded with nano primer, the presence of the smear plugs occluding the dentinal tubules was shown. This observation was in agreement with Coutinho and others 1 and Korkmaz and others 19 who reported no evidence of demineralization or hybrid layer formation and the absence of cement extensions inside the dentinal tubules.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the SEM photomicrograph of the fractured surface of the nano-filled RMGI bonded with nano primer, the presence of the smear plugs occluding the dentinal tubules was shown. This observation was in agreement with Coutinho and others 1 and Korkmaz and others 19 who reported no evidence of demineralization or hybrid layer formation and the absence of cement extensions inside the dentinal tubules.…”
Section: Discussionsupporting
confidence: 82%
“…This might be attributed to the absence of the intermediate adhesive layer following the application of the nano primer. 19 One-step self-etch adhesives did not meet the clinical predictions in terms of their bond durability, as high incidence of failure during their clinical service was reported. 3 One-step self-adhesives could bond resin composite to dentin, statistically, with the same results as the etch-and-rinse adhesives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding bond strength studies, SE has resulted in statistically higher dentin bond strengths than EB. 30 The bond strengths obtained with SE are not affected by thermal fatigue when bonded to coronal dentin 31 ; this may be a result of minimal residual water left entrapped within the dentin-adhesive interface.…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, previous studies have reported that RMGIs have SBS values greater than glass ionomer materials but less than composites. 18,19 Therefore, it would be expected that conditions that enable a RMGI to behave like a The failure analysis revealed that more of the light-cured specimens of FII and KN failed by cohesive and mixed failures. This result further indicates that a stronger bond was formed between light-cured RMGI and dentin than uncured RMGI and dentin.…”
Section: Discussionmentioning
confidence: 99%